SEJARAH KEBUDAYAAN ISLAM: DARI MASA KEJAYAAN HINGGA MASA KINI - Roqib; Romdlon, Hariyadi (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
This article explores the development of Islamic culture from its golden age to the present day. During its peak, the Islamic world became a center of knowledge, philosophy, art, and architecture. However, due to various internal and external factors, this cultural flourishing eventually declined. In recent times, Islamic culture has been undergoing transformation and revival, especially through education, technology, and contemporary intellectual movements. This study aims to understand the historical dynamics of Islamic culture and examine the challenges and opportunities it faces in the modern era